Land of France 1815-1914. - Clout, Hugh D. (Routledge Library Editions: Rural History ;, 2017)
"This book, first published in 1983, attempts to examine the rural change in France between 1815 and 1914 with a sustained and explicit spatial approach. This volume represents a position in which space and time are meshed in an analysis of the forces underlying land-use and other changes that have contributed much to the making of the French landscape. In this book the shift from the rural economy towards the urban markets in this period is examined thoroughly, using the vast statistical record of cadastral surveys and agricultural enquiries as well as contemporary reports and agricultural journals. The detailed mapping of historical data is a major feature of the treatment. As a scholarly account of a major topic in historical geography, The Land of France 1815-1914 should appear to all students and researchers with interests in historical and rural geography and economic history and especially those specialising in European studies."--Provided by publisher.